The circumgalactic medium of Milky Way-like galaxies in the TNG50 simulation - I: halo gas properties and the role of SMBH feedback - Ramesh, Rahul; Nelson, Dylan; Pillepich, Annalisa (Monthly notices of the Royal Astronomical Society, 2023)
We analyse the physical properties of gas in the circumgalactic medium (CGM) of 132 Milky Way (MW)-like galaxies at z = 0 from the cosmological magneto-hydrodynamical simulation TNG50, part of the IllustrisTNG project. The properties and abundance of CGM gas across the sample are diverse, and the fractional budgets of different phases (cold, warm, and hot), as well as neutral H i mass and metal mass, vary considerably. Over our stellar mass range of $10^{10.5} < M_\star /{\rm M}_\odot < 10^{10.9}$, radial profiles of gas physical properties from $0.15 < R/R_{\rm 200c} < 1.0$ reveal great CGM structural complexity, with significant variations both at fixed distance around individual galaxies, and across different galaxies. CGM gas is multiphase: the distributions of density, temperature, and entropy are all multimodal, while metallicity and thermal pressure distributions are unimodal; all are broad. We present predictions for magnetic fields in MW-like haloes: a median field strength of $|B|\sim 1\,μ{\rm G}$ in the inner halo decreases rapidly at larger distance, while magnetic pressure dominates over thermal pressure only within ${\sim}0.2 × R_{\rm 200c}$. Virial temperature gas at ${\sim}10^6\,{\rm K}$ coexists with a subdominant cool, $\lt 10^5\,{\rm K}$, component in approximate pressure equilibrium. Finally, the physical properties of the CGM are tightly connected to the galactic star formation rate, in turn dependent on feedback from supermassive black holes (SMBHs). In TNG50, we find that energy from SMBH-driven kinetic winds generates high-velocity outflows (≳500-2000 km s−1), heats gas to supervirial temperatures (>106.5-7 K), and regulates the net balance of inflows versus outflows in otherwise quasi-static gaseous haloes.
Online veröffentlicht 2022 December 2
Gesehen am 27.03.2023